1980
DOI: 10.1002/1097-0142(19800301)45:5<948::aid-cncr2820450519>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biochemical markers in patients with gynecologic malignancies

Abstract: Plasma levels of carcinoembryonic antigen (CEA), alpha-fetoprotein (AFP), and human chorionic gonadotropin (hCG) were measured in 253 patients with gynecologic malignancies and in 317 patients with benign gynecologic diseases. Plasma concentrations of each of these antigens were elevated in a significantly (p less than 0.001) greater number of patients with invasive gynecologic cancers than in the control population. Carcinoembryonic antigen was the most commonly elevated marker, followed by AFP and hCG. Prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…AFP is a tumour marker which is positive in all cases of endodermal sinus tumour, a germ cell tumour of ovary (Van Nagell et al 1981). Moderate elevation of AFP was found in 43% of advanced epithelial ovarian cancer by Donaldson et al (1980). As in our study, no consistent correlation was found between changes in marker level and the course of the disease (Stanhope et al 1979).…”
Section: Discussioncontrasting
confidence: 68%
“…AFP is a tumour marker which is positive in all cases of endodermal sinus tumour, a germ cell tumour of ovary (Van Nagell et al 1981). Moderate elevation of AFP was found in 43% of advanced epithelial ovarian cancer by Donaldson et al (1980). As in our study, no consistent correlation was found between changes in marker level and the course of the disease (Stanhope et al 1979).…”
Section: Discussioncontrasting
confidence: 68%
“…For example, both Evi-l and Epo are expressed in the tubular cells in the kidney (34). In addition, both Evi-J (38) and human chorionic gonadotropin (16) have been found to be expressed in human endometrial carcinomas. We are currently investigating the significance of these findings.…”
Section: T S Ac a A A T A A C A S A C Aa B A T A A C A S A C Aa S A Tmentioning
confidence: 99%
“…Although mild or moderate elevations in serum CA125 may be seen with other histological types of ovarian carcinoma, such as endometrioid or clear cell, markedly elevated levels are characteristic of serous carcinoma. Ovarian mucinous neoplasms are less frequently associated with an elevated serum CA125 than non-mucinous tumours5 and levels are typically within the normal range or mildly elevated 6 7. In most ovarian mucinous neoplasms with an elevated serum CA125, it is likely that the CA125 is secreted by reactive mesothelial cells, which are commonly seen in the omentum of patients with ovarian mucinous tumours, rather than by the tumour cells themselves since immunohistochemically the neoplastic cells are usually CA125 negative (W Glenn McCluggage, personal observations).…”
Section: Introductionmentioning
confidence: 99%